Community Service through Building Defect Inspection: Assessing Building Conditions of Orphanages in Cikarang, Indonesia - Seng Hansen; BMAS Anaconda Bangkara; Lydia Darmiyanti; Ivan Imanuel; Prihartono; Eddy T. Sudjatmiko; Ika Bali (Altifani Journal: International Journal of Community Engagement, 2025)
This community service project was conducted by civil engineering students and lecturers from President University to assess the physical condition of two orphanages in Cikarang, Indonesia. The project focused on identifying visible building defects that may pose risks to safety, comfort, or health. Using non-invasive methods such as visual inspection, photographic documentation, and staff interviews, the students evaluated structural components, material conditions, and environmental factors at Rumah Harapan Graha Asri and Panti Asuhan Rumah Singgah Anak Berkat. Key findings included peeling paint, moisture-induced wall cracks, mold growth, unstable plywood flooring, and deteriorating wooden staircases. These issues were largely attributed to prolonged exposure to humidity, poor construction practices, and the absence of regular maintenance. The proposed actionable recommendations include waterproofing treatments, structural reinforcement, mold remediation, safety improvements, and the implementation of a simple maintenance plan. This project highlights the importance of building defect assessments in community-based facilities and demonstrates how civil engineering students and lecturers can contribute meaningfully to public welfare. It also served as a practical learning experience, allowing students to apply classroom knowledge in a real-world context. The outcomes reinforce the need to integrate social responsibility and technical training into engineering education.